2021
DOI: 10.1042/cs20201091
|View full text |Cite
|
Sign up to set email alerts
|

DUSP12 acts as a novel endogenous protective signal against hepatic ischemia–reperfusion damage by inhibiting ASK1 pathway

Abstract: Ischemia–reperfusion injury (IRI) consequent to major liver surgery is a still unmet clinical problem. The activation of endogenous systems of hepatoprotection can prevent the damaging effects of ischemia–reperfusion (IR) as shown by the phenomenon known as ‘ischemic preconditioning’. The identification of endogenous signal mediators of hepatoprotection is of main interest since they could be targeted in future therapeutic interventions. Qiu et al. recently reported in Clin. Sci. (Lond.) (2020) 134(17), 2279–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…We found that the stimulation of ASK1, that is induced at the time of reoxygenation by ER stress, is increased by hepatocellular steatosis through an ROS-dependent mechanism, and we showed that such increased ASK1 activation promoted liver inflammation and exacerbated JNK-dependent hepatocyte damage [10]. These findings indicate that pharmacologic interventions targeting ASK1 stimulation are a promising approach to protect against surgically induced IRI in humans, in both normal [8,9] and fatty livers.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…We found that the stimulation of ASK1, that is induced at the time of reoxygenation by ER stress, is increased by hepatocellular steatosis through an ROS-dependent mechanism, and we showed that such increased ASK1 activation promoted liver inflammation and exacerbated JNK-dependent hepatocyte damage [10]. These findings indicate that pharmacologic interventions targeting ASK1 stimulation are a promising approach to protect against surgically induced IRI in humans, in both normal [8,9] and fatty livers.…”
Section: Introductionmentioning
confidence: 59%
“…The Apoptosis Signal-Regulating Kinase 1 (ASK1) is a master and upstream inductor of IRI in liver and in extrahepatic tissues [7][8][9] and both OS and ER stress are among the 2 of 12 factors that are able to induce ASK1 stimulation [7,9]. Consistently, we previously showed that the increased damage and inflammation of fatty liver that is exposed to IR is directly related to an enhanced ASK1 activation [10].…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations